Assessment of linguistic competence in children with hearing loss: an analysis based on the communication modality employed - Durán-Bouza, Montserrat; Pernas, Lorena; Brenlla-Blanco, Juan-Carlos (Anales de Psicología / Annals of Psychology, 2024)
The main objective of this study was to examine the neuropsychological and linguistic differences in a sample of deaf children compared to their hearing peers. Additionally, it sought to evidence possible differences among children with hearing loss considering the type of intervention received to promote language and communication. The sample consisted of 124 participants, of whom 64 had hearing loss and 60 were hearing. The age range in both groups was 5 to 11 years. The Clinical Evaluation of Language Fundamentals –CELF5- test was used to obtain data on linguistic and neuropsychological skills. The results obtained showed that the performance of children with hearing loss, was lower than that of their hearing peers. When comparing the types of communication modalities used by the deaf children, it was found that those who used total communication scored higher than those who used oral language and those who used Spanish sign language. These results support the use of early intervention that includes the use of support systems to facilitate oral language learning. That is, systems should be included that promote learning based on grammatical structure, semantic and pragmatic aspects like those of the spoken language.